Medical education and physician training in the era of artificial intelligence - Yueyuan Xu; Zehua Jiang; Daniel Shu Wei Ting; Alfred Wei Chieh Kow; Fernando Bello; Josip Car; Yih-Chung Tham; Tien Yin Wong (Singapore Medical Journal)
With the rise of generative artificial intelligence (AI) and AI-powered chatbots, the landscape of medicine and healthcare is on the brink of significant transformation. This perspective delves into the prospective influence of AI on medical education, residency training and the continuing education of attending physicians or consultants. We begin by highlighting the constraints of the current education model, challenges in limited faculty, uniformity amidst burgeoning medical knowledge and the limitations in ‘traditional’ linear knowledge acquisition. We introduce ‘AI-assisted’ and ‘AI-integrated’ paradigms for medical education and physician training, targeting a more universal, accessible, high-quality and interconnected educational journey. We differentiate between essential knowledge for all physicians, specialised insights for clinician-scientists and mastery-level proficiency for clinician-computer scientists. With the transformative potential of AI in healthcare and service delivery, it is poised to reshape the pedagogy of medical education and residency training.